Utilization of palm oil waste into fired clay brick - Abdul Kadir, Aeslina; Mohd Zahari, Nur Azian; Mardi, Noor Azizi (AENSI Publishing Corporation, 2012)
Malaysia is one of the largest palm oil producers, contributing approximately 50% of the world palm oil production. In the process of palm oil extraction, biomass materials such as Palm Fibre (PF), Palm Kernel Shell (PKS) and Palm Oil Fuel Ash (POFA) are produced annually and increasingly becoming a threat to the environment. This study investigated the utilization of three types of palm oil waste (POW) into fired clay bricks. The effects of POW incorporation on the properties of bricks were determined. Bricks were manufactured by incorporating 3% of different types of POW (PKS, POFA and PF) and fired at 1050°C with a heating rate of 1°C/min. All bricks were tested for their physical and mechanical properties including drying and firing shrinkage, dry density, initial rate of suction, compressive strength and thermal conductivity. In addition, energy efficiency of the brick firing process was also calculated from its calorific value. All three types of POW decreased the manufactured bricks’ compressive strength but increased their dry shrinkage and initial rate of suction (IRS) as a result of increased porosity value. Nonetheless, the incorporation of POW into a clay brick has improved its thermal conductivity properties and energy efficiency during manufacturing. In conclusion, POWs can be considered for producing lightweight fired clay bricks as they could act as pore formers to improve the thermal properties and energy efficiency in brick firing process.